Overtreatment of older people with type 2 diabetes—a high impact frequent occurrence in need of a new definition. Issue 2 (6th November 2022) - Christiaens, Antoine; Henrard, Séverine; Boland, Benoit; Sinclair, Alan J.
Abstract: Background: Diabetes overtreatment is a frequent and major issue in older people with type 2 diabetes but its definition is often inconsistent and may be misleading. This critical review has aimed at examining the definitions of diabetes overtreatment in older people used in research studies. Methods: Studies addressing diabetes overtreatment in people aged 65 or older were identified by searching the PubMed database according to an extensive search equation. Results: Twenty‐two research studies providing a definition of diabetes overtreatment in people aged were found. Overall, 12 different definitions of diabetes overtreatment were used. All studies defined overtreatment according to a HbA1c threshold (varying from <42 mmol/mol [<6.0%] to <64 mmol/mol [<8%]). Amongst them, 2 definitions had no consideration about glucose‐lowering (GL) treatment, 6 required the prescribing of ≥1 GL agent(s), and 4 the prescribing of ≥1 GL agent(s) inducing the high risk of hypoglycaemia (i.e., sulfonylurea(s) or insulin(s)). Only 4 definitions (four studies) were individualised, using varying HbA1c thresholds according to patients' age or health status. Conclusions: Definitions of diabetes overtreatment are heterogeneous across research studies, which is confusing. A standardised definition, based on the individual risk of hypoglycaemia and/or its complications must be promoted in order to bring clarity and greater insight into this field, as well as to improve the quality of management of diabetes in older patients.